Droplet dynamic characteristics on PEM fuel cell cathode gas diffusion layer with gradient pore size distribution. (November 2021) - Wang, Yulin; Wang, Xiaodong; Wang, Xiaoai; Liu, Tao; Zhu, Tingting; Liu, Shengchun; Qin, Yanzhou
Abstract: Understanding of droplet dynamic characteristics on gas diffusion layer (GDL) of polymer electrolyte membrane (PEM) fuel cell is of great importance for cell performance improvement. This study comprehensively investigated droplet dynamic characteristics on fuel cell cathode GDL with gradient pore size distribution (GPSD). The influence of different pore sizes, GPSD and wettabilities of GDL on droplet dynamic characteristics is numerically evaluated by using the volume of fluid (VOF) method through the analysis of the interaction among the forces over droplet. Results indicate that droplet has a relatively short detachment time and a smaller detachment radius on superhydrophobic and superhydrophilic GDLs compared with on a moderately hydrophobic GDL regardless of pore size. Moreover, large pores can facilitate droplet detachment, but increase droplet detachment radius and pressure drop. Compared with uniform (U)PSD, for transverse (T)-GPSDs with a small pore distance at a relatively low airflow velocity or a large pore distance at a high airflow velocity, or for the longitudinal (L)-GPSD with a large pore in the upstream and a small pore in the downstream at a large pore distance, the droplet detachment time decreases by 34.3% and 25.2% with a reduction of pressure drop, respectively.